Penyelesaian Utang-Piutang Melalui Gugatan Sederhana (Small Claim Court) Sebagai Implementasi Azas Peradilan Sederhana Cepat dan Biaya Ringan di Pengadilan Negeri Kudus - Sutahar Sutahar (Syntax Idea)
The shift of social life from local realities towards national and global dimensions adds complexity to the handling of disputes. Although the law seeks to resolve disputes, there are still instances of failures in dispensing justice. In this context, the government has endeavored to improve the substance, structure, and legal culture through medium-term development policies. The research objective of this paper is likely to evaluate and analyze the effectiveness of the implementation of Supreme Court Regulation Number 4 of 2019 concerning the Procedure for Simple Lawsuits in the Kudus District Court. The approach used is sociological juridical or non-doctrinal legal research, involving field observations and studies on the functioning of the law in society. Primary data was obtained through structured interviews with judges, litigants, and legal representatives at the Kudus District Court. Meanwhile, secondary data, as supporting information, was obtained through literature studies covering legislation and relevant court decisions. Data collection methods included field research with participant observation and interviews, as well as literature research. Data analysis was conducted qualitatively to narrow down and limit the data according to the core issues under investigation. This study notes that the Kudus District Court has been implementing simple lawsuits since the enforcement of Supreme Court Regulation Number 2 of 2015, later updated by Supreme Court Regulation Number 4 of 2019. While further evaluation is still needed to comprehensively assess the effectiveness of the Simple Lawsuit implementation, the regulatory changes indicate the government's and judicial institutions' efforts to enhance the quality and efficiency of dispute resolution in Indonesia.